Etiology of Severe Anemia in Children at a Tertiary Care Hospital. - Suresh Babu Mendu; Vedavyasa Srigade (Asian Journal of Clinical Pediatrics and Neonatology, 2018)
Background: Public health significance of anemia in children was classified as severe in India. Severe anemia (Hb < 7g/dL) significantly increases the risk of death. Critical diagnostic evaluation and a thorough work-up make the accurate diagnosis of intrinsic red cell abnormalities feasible. Review of etiology helps to formulate strategies to prevent them, and to know the degree of achievement of the targets. Objectives: The aim of the present study was to identify the etiology of severe anemia. Subjects and Methods: It is a retrospective record based study done at a tertiary care center. All new severe anemia cases aged 1 month to 18 yrs, which were admitted on Monday from Jan 2017 to Dec 2017 were included. Previously worked up cases coming for transfusions and anemia due to bleeding were excluded. Details of history, physical examination and work-up were obtained for justification of diagnosis based on existing evidence. Results: 112 children were included. Mean age was 3.94 yrs (+/_3.52) (Range: 1 month-13 years), median and mode were 3 years. Male to female ratio was 1.95:1.  51% of severe anemia cases were due to iron deficiency. 11.6% had confirmed ?-Thalassemia Trait (BTT) and 18.75% had suspected Thalassemia Trait (TT). Other causes of severe anemia were: folate deficiency (13.4%), B12 deficiency (1.8%), hereditary spherocytosis (HS) (7.1%), marrow replacement by acute leukemia (6.25%), aplastic anemia         (2.7%), malaria (2.7%), and antiretroviral therapy induced anemia (0.9%). HS was the second most common cause of hemolytic anemia after thalassemias. Conclusion: Though a number of nutrition based initiatives have been initiated in the country, the burden of preventable iron deficiency, contributing to severe anemia cases is enormous, signifying the need for more effective programs to be implemented in India. Folate should be supplemented to all children with anemia irrespective of the cause. Essential workup with proper interpretation of investigations for arriving at diagnosis prior to transfusing the child is obligatory.